Predicting rodent impact in crop fields by near-infrared reflectance spectroscopy analysis of their diet preferences - Heroldová, M. (Marta); Čižmář, D.; Tkadlec, E. (Emil) (Crop Protection, 2010)
Prediction of impact by NIRS analysis of rodent diet preferences was evaluated in four dominant field rodents in Moravia farmland (Czech Republic). These are the common vole (Microtus arvalis), pygmy field mouse (Apodemus uralensis), wood mouse (Apodemus sylvaticus), and black-striped field mouse (Apodemus agrarius). This method predicts the proportions of food components consumed, based on a calibration equation developed through feeding tests in the laboratory. The two types of monofood feces collected from mice that were fed with either barley or wheat grain were mixed to form a series of increasing proportions of wheat feces subsequently measured by NIRS. The calibration equation was then applied to other mice but a separate calibration equation had to be developed for the common vole. Then we compared feces from preference test to the calibration equation. Proportion of wheat preference by all mouse predict stronger impact of these in wheat fields in ripe stage than in barley one.